2002
DOI: 10.1111/j.0004-8666.2002.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of urokinase‐type plasminogen activator and its inhibitor type 1 (PAI‐1) in squamous cell carcinoma of the uterine cervix

Abstract: The results indicate, that PAI-1 expression is of some prognostic impact in cervical cancer, indicating an association of elevated PAI levels with local tumour progression and reduced recurrence-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…Because all the patients in their group were of a FIGO stage II disease, comparisons between stages could not be made, nor was the relationship with other parameters evaluated. In another study by Horn et al .,38 PAI‐1 expression in 114 cervical cancer patients (FIGO stage I to III) was evaluated and, corresponding with our study, elevated PAI‐1 levels were demonstrated to be positively correlated with advanced tumor stage. However, after including other prognostic parameters in their multivariate analysis, PAI‐1 failed to give additional prognostic information regarding survival rates, which is in contrast to our findings.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Because all the patients in their group were of a FIGO stage II disease, comparisons between stages could not be made, nor was the relationship with other parameters evaluated. In another study by Horn et al .,38 PAI‐1 expression in 114 cervical cancer patients (FIGO stage I to III) was evaluated and, corresponding with our study, elevated PAI‐1 levels were demonstrated to be positively correlated with advanced tumor stage. However, after including other prognostic parameters in their multivariate analysis, PAI‐1 failed to give additional prognostic information regarding survival rates, which is in contrast to our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Overproduction of both factors has been associated with poor survival in a large variety of cancers 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38. Data on the role of these 2 factors in cervical carcinogenesis are conflicting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overproduction of both factors has been associated with a worse prognosis in a broad variety of cancer diseases. 27,28 Within this report, the PAI-1-TGF-A1 genes in the group of patients showed a high LD value (71%, P G 0.001).…”
Section: Discussionsupporting
confidence: 50%
“…There is increasing evidence for PAI in cancer metastasis independent of its protease inhibitory activity, such as tumor cell motility, cell and anti-cell adhesion, pro- and anti-angiogenesis, and prevention of apoptosis [37]. In cervical cancer, increased levels of uPA and PAI-1 proteins were detected in cervical tumor extracts but not in normal tissue extracts [38] and are linked to poor prognosis [39]. In this study, we revealed that AP extracts decreased protein levels of tumor metastasis-related proteins such as MMP-9 and u-PA in KB cells.…”
Section: Discussionmentioning
confidence: 99%